Cultures of Carbon and the Logic of Care: The Possibilities for Carbon Enrichment and Its Cultural Signature. Issue 4 (4th July 2017) - Jackson, Sue; Palmer, Lisa; McDonald, Fergus; Bumpus, Adam
Abstract : Climate change and the associated need to decarbonize pose not just risks to cultures but potential opportunities for cultural experimentation, renewal, and economic dynamism. An Australian case of carbon mitigation through carbon farming represents a discursive tool with which indigenous groups are seeking to leverage a very distinct conceptualization of payment for ecosystem services, one that values the labor and reciprocal relationships and logic of care required to abate or sequester carbon. Inscribed with an inalienable ancestral cultural signature, the indigenous produced carbon offsets being promoted by indigenous carbon market participants represent more than a mere carbon reduction; they initiate processes of potentially enduring exchange and engagement. This carbon signature works to enrich carbon as well as embed peoples' relations with it, with each other, and with the places from which the offset is generated. Contributing to emergent research into cultures of carbon, it is our conjecture that valorizing these relations in ethical exchanges is a potentially productive way of financing alternative approaches to environmental stewardship. The insights signal potential prospects for other marginalized cultures to appropriate, repurpose, and benefit from mainstream decarbonization strategies and participate in climate governance.